การใช้คอมพิวเตอร์วิเคราะห์ระบบไฟฟ้ากำลังโดยวิธีไดกอบติค : รายงานผลการวิจัย - สุขุมวิทย์ ภูมิวุฒิสาร (จุฬาลงกรณ์มหาวิทยาลัย, 1983)
In this paper a diakoptic method or a piecewise solution was derived and applied to the solution of short circuit, economic operation and transient stability problems of large-scale power system. This method divides a power system into several smaller subsystems, finds the solution models for the subsystems, and finally obtains the solution of the original power system through an interconnection model. This method will render advantages in computer storage, and it can be used to analyse a large-scale power system with available digital computer.